Study of Changes in Coastal Morphology Due to Utilization of the Surabaya City Coastal Area - Sujantoko; Widi Agus Pratikto; Rudi Waluyo Prastianto; Muh. Ilham Maulana; Anggie Vibriyanti (International Journal of Marine Engineering Innovation and Research, 2022)
Indonesia is an archipelagic country with a vast coastal area, so proper management is needed in the development of coastal areas. The city of Surabaya is one of the cities that carry out the development of coastal areas by projecting strategic areas of its coastal areas as regulated in the regional medium-term development plan 2016-2021. The strategic area of the coastal area of Surabaya city is divided into two, namely strategic areas to support economic growth and save the environment. One of the efforts to optimize the development of coastal areas is to examine changes in coastal morphology due to coastal utilization. Analysis of the study was carried out by comparing historical maps of the last 10 years with existing maps from google earth and map analysis using ArcGIS 10.8. The results show that most in the coastal area of north Surabaya there is a change in coastal morphology covering an area of 360,121 m2 as a result of the reclamation of the construction of the Lamong bay port and 623.12 m2 in the coastal area of east Surabaya due to the addition of mangroves. Regular monitoring and improvement efforts on the coast of Surabaya city must be carried out on an ongoing basis, so that coastal threats such as sedimentation and erosion can be minimized.